ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI KINERJA KARYAWAN BAGIAN AKUNTANSI PADA KOPERASI SIMPAN PINJAM DI KABUPATEN KARANGASEM - I Gusti Ayu Asri Pramesti; I Wayan Sudana (Jurnal AKSES, 2019)
Employee performance is the achievement or work performance of an employee, both in quality and quantity for the tasks assigned to him. This study aims to re-examine the effect of the variable effectiveness of the accounting information system, work motivation, technical ability of the user of accounting information systems and compensation for employee performance accounting section of the Koperasi Simpan Pinjam in Karangasem District.The sample in this study were 42 Koperasi Simpan PInjam which were guided by Dinas Koperasi dan UKM Kabupaten Kararangasem. Determination of the sample using purposive sampling method. The analytical tool used is multiple linear regression analysis. The results of the study show the effectiveness of information systems, work motivation and compensation have a positive effect on the performance of employees in the accounting department. While the technical capabilities of the users of accounting information systems do not affect the performance of employees in accounting